Sex-specific association of poor sleep quality with gray matter volume. Issue 9 (6th March 2020) - Neumann, Nicola; Lotze, Martin; Domin, Martin
Abstract: Study Objectives: Previous studies were inconsistent with regard to the association of sleep dysfunction on the brain's gray matter volume (GMV). The current study set out to investigate if there is a moderating effect of sex on the relationship between sleep quality in healthy individuals and GMV. Methods: We applied voxel-based morphometry in 1, 074 young adults of the "Human Connectome Project." An analysis of variance with the factors "sleep quality" (good/poor according to the Pittsburgh Sleep Quality Index, cutoff >5) and "sex" (male, female) on GMV was conducted. Additionally, linear relationships between sleep quality and GMV were tested. Results: The analysis of variance yielded no main effect for sleep quality, but an interaction between sex and sleep quality for the right superior frontal gyrus. Post hoc t -tests showed that female good sleepers in comparison to female poor sleepers had larger GMV in the right parahippocampal gyrus extending to the right hippocampus (whole-brain family-wise error [FWE]-corrected), as well as smaller GMV in the right inferior parietal lobule (whole-brain FWE-corrected) and the right inferior temporal gyrus (whole brain FWE-corrected). There were no significant effects when comparing male good sleepers to male poor sleepers. Linear regression analyses corroborated smaller GMV in the right parahippocampal gyrus in women with poor sleep quality. Conclusions: Poor sleep quality was associated with altered GMV in females, but not in males. Future studies are needed to investigate the neurobiological mechanisms that underlie the sex differences in the association of sleep quality and brain differences found in this study.